Cellulose nanofibers as effective binders for activated biochar-derived high-performance supercapacitors. (1st February 2023) - Mian, Md Manik; Kamana, Ishimwe Marie Louise; An, Xingye; Abbas, Syed Comail; Ahommed, Md Sohel; He, Zhibin; Ni, Yonghao
Abstract: Traditional hydrophobic binders can limit supercapacitors' performance by impeding ion accessibility. Herein, we demonstrate the potential of plant-derived environmentally friendly Cellulose Nanofibers (CNF) as binders for biochar (BN-Ac)-based supercapacitors. The CNF binder retains BN-Ac's micropores and improves wettability, while the Polyvinylidene Fluoride (PVDF) binder fills micropores and hinders ion-conductive pathways. The as-synthesized BN-Ac/CNF exhibits a capacitance of 268.4 F g −1 at 5 A g −1, which is 1.4 times higher than that of BN-Ac/PVDF. In addition, the energy density improves from 4.6 to 5.7 Wh kg −1 at 2.1 and 2.5 kW kg −1 power, respectively, for replacing PVDF with CNF. More importantly, BN-Ac/CNF shows outstanding capacitance retention of 96.2 % after 10, 000 charge/discharge cycles. The improved wettability and reduced bulk electrolyte resistance by hydrophilic CNF binders are responsible for the electrode's high capacitance. Concurrently, this study showcases a facile strategy for improving supercapacitor performance and a green application of CNF in energy devices. Graphical abstract: Unlabelled Image